Critical Autoethnography as an Empowering Discourse for International Students in US Higher Education - Hyesun, Cho; Jiahong, Wang; Erlinda, Mikal; Chang, Liu (IGI Global, 2023)
Despite the increasing number of international students in colleges and universities in the United States, there is a scarcity of research that informs higher education instructors on how to create a space for these students to share their challenges. This chapter illustrates how critical autoethnography serves as an empowering academic discourse for international students in higher education. Drawing from linguicism and transnational habitus, it elucidates how graduate students internalize and resist linguicism while also exercising teacher agency by using transnational habitus in language classrooms. By sharing their stories in relation to power imbalance in social interactions, this chapter illustrates ways in which university teachers can promote culturally and linguistically sustaining written discourse practices for international students, using a critical autoethnography.